Uji Efektivitas Soda Pinus Sebagai Agen Antimikroba Alami Menggunakan Metode Difusi Cakram - Agistha Dwi Lestari; Ardi Mustakim (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Pine soda is a natural fermented liquid from pine needles (Pinus merkusii) which has a distinctive aroma and contains bioactive compounds with potential as antimicrobial agents. This study aims to determine the antibacterial activity of pine soda against Staphylococcus aureus using the disc diffusion method and to compare its effectiveness with the antibiotic ampicillin as a positive control. The process of making pine soda is carried out through simple fermentation of Pinus merkusii pine needles under certain conditions to produce a fragrant liquid. Furthermore, qualitative tests are carried out to identify the content of bioactive compounds, such as flavonoids, phenols, and essential oils, which are known to have antibacterial properties. In the antibacterial activity test, paper discs that have been soaked in pine soda solutions with graded concentrations (2%, 4%, 6%, 8%, and 10%) are placed on agar media that have been inoculated with S. aureus. The results of the observation showed the presence of inhibition zones in each treatment with varying sizes. The largest inhibition zone was obtained at a concentration of 10% with a diameter of 10 mm, which is included in the medium inhibition category. As a comparison, ampicillin produced an inhibition zone of 26.3 mm, while distilled water, the negative control, showed no inhibition zone. These findings indicate that the antibacterial activity of pine soda is influenced by its bioactive compound content, although its effectiveness is still lower than that of standard antibiotics. This potential opens up opportunities for developing pine soda as a safe natural antibacterial agent, whether in the form of health products such as antiseptics, natural cleaners, or functional beverages that support body health. Further research is needed to optimize the fermentation process, increase the concentration of active compounds, and test its effectiveness against various types of pathogenic bacteria.